A stepwise approach to facilitate adoption of climate smart practices for smallholder coffee production in Uganda - Mukasa, D.; Rusinamhodzi, L.; van Asten, P.J.A.; Amwonya, D.; Sseguya, H.; Okiror, F.A.; Kirungi, D.; Wodada, W.; Komakech, V.; Margiotta, S.; Jassogne, L. (Informa UK Limited, 2025)
Adoption of Climate-smart Agricultural Practices (CSA) enhances crop productivity and livelihoods. Smallholder coffee farmers in Uganda receive training on good agricultural practices (GAPs) through extension programs, but adoption remains low. Adopting all ‘best practices’ at once may be unrealistic for resource-limited, risk-averse smallholders. This study tested a Stepwise approach, breaking GAPs into manageable, incremental investments. Field trials were conducted in Luweero (Central) and Sironko (East) districts of Uganda, with 16 demonstration sites using randomized treatments and the control (farmer practice), divided into four steps. Each site served 25–30 farmers through experiential learning. A co-design method ensured farmer involvement in the design, development, and testing for sustainability. Results from two harvests (2018–2019) showed significant cumulative yield gains over the control. Arabica yields increased by 31%, 43%, 54% and 65% across Steps 1-4,. Robusta showed gains of 7%, 22%, 23% and 39% respectively. Marginal rate of returns (MRR) was relatively high for Step 1 (563%), 2 (169%) and 4 (122%) for Robusta coffee , and 221%, 217% and 485% for Step 2, 3 and 4 for Arabica coffee respectively. The Stepwise approach demonstrated improved yield gains and increased farmer income.